Niższe Seminarium Duchowne we Włocławku – założenia instytucjonalne i edukacyjne (1908–1988) - Lisowska, Kinga (Biuletyn Historii Wychowania, 2019)
This article focuses on the operation of the Lower Seminary in Włocławek in the 20th century. It is an example of a formative and educational institution subordinated simultaneously to the Church and the government. For the entire period of its existence, the school was the property of the Włocławek Diocese. The organization of the seminary and the education was provided in complex social, political and systemic circumstances. In the course of its operation, the school was dependent on Russian, Polish and German authorities. The article presents the history of the Lower Seminary, the organizational and curricular changes as well as the organization’s basic structure. The history of the Seminary is a part of research into private education in the 20th century in Poland, encompassing the lower secondary and secondary school levels. The research also contributes to our knowledge of the organization of education in the Lower Seminary in Włocławek, as well as ecclesiastic education in lower seminaries in Poland in the 20th century.